2018
DOI: 10.1002/cjp2.119
|View full text |Cite
|
Sign up to set email alerts
|

Combined epithelial marker analysis of tumour budding in stage II colorectal cancer

Abstract: Tumour budding predicts survival of stage II colorectal cancer (CRC) and has been suggested to be associated with epithelial‐to‐mesenchymal transition (EMT). However, the underlying molecular changes of tumour budding remain poorly understood. Here, we performed multiplex immunohistochemistry (mIHC) to phenotypically profile tumours using known EMT‐associated markers: E‐cadherin (adherence junctions), integrin β4 (ITGB4; basement membrane), ZO‐1 (tight junctions), and pan‐cytokeratin. A subpopulation of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Tumour budding is one of the initial steps of cancer invasion and metastasis, as budding cells migrate through the extracellular matrix, invade lymphovascular structures, and form metastatic tumour colonies in lymph nodes and distant organs 34 , 35 , 36 . During this process called epithelial mesenchymal transition (EMT), activation of WNT/CTNNB1 signalling occurs in tumour cells, which lose expression of epithelial markers such as CDH1 expression and instead express genes more commonly associated with mesenchymal cells, such as CDH2 (cadherin 2, N-cadherin) and VIM (vimentin) [ 2 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumour budding is one of the initial steps of cancer invasion and metastasis, as budding cells migrate through the extracellular matrix, invade lymphovascular structures, and form metastatic tumour colonies in lymph nodes and distant organs 34 , 35 , 36 . During this process called epithelial mesenchymal transition (EMT), activation of WNT/CTNNB1 signalling occurs in tumour cells, which lose expression of epithelial markers such as CDH1 expression and instead express genes more commonly associated with mesenchymal cells, such as CDH2 (cadherin 2, N-cadherin) and VIM (vimentin) [ 2 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that there was a significant correlation between a high expression level of SE and the tumor budding status and invasion depth in the CRC. Tumor budding has been suggested to be associated with EMT, as evidenced by decreased or aberrant expression of E-cadherin [39,40]. The SE and E-cadherin protein expression pattern in the tumor budding of the CRC was determined by immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for PanEpi channel was set manually to exclude all of the stromal area based on visual inspection. The PanEpi detection included staining and detection of two different anti‐pan‐cytokeratin antibody clones (AE1/3 and C‐11) and anti‐E‐cadherin antibody (clone 36) for optimal epithelium coverage . Stromal cells were classified as fibroblasts (VIM‐pos, aSMA‐neg), myofibroblasts (VIM‐pos, aSMA‐pos), or smooth muscle (aSMA‐pos, VIM‐neg) (Figure ; Figure S1).…”
Section: Methodsmentioning
confidence: 99%